IMPROVING THE ACCOUNTABILITY OF SMEs IN MALANG CITY: A STRATEGIC STEP TOWARDS GLOBAL COMPETITIVENESS - Pangesti, Nitami Galih; Soemarsono, Prinintha Nanda; Eriani, Izmi Dwira (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The low level of financial literacy among MSMEs directly impacts poor accountability practices. Without a sufficient understanding of basic accounting concepts, MSMEs struggle to record transactions systematically and accurately. Their ability to prepare comprehensive financial statements is crucial not only for meeting internal requirements but also for enhancing competitiveness on a global scale. To address the issues related to accountability practices, educational efforts on balance sheets, income statements, and the preparation of application-based financial reports are essential. The community service activity titled "Enhancing Accountability of Micro, Small, and Medium Enterprises in Malang City to Support Global Competitiveness" was conducted on Sunday, July 14, 2024, at the Malang Creative Center, involving 22 MSMEs that are members of the Malang Small Traders Association (Paguyuban Seduluran Sak Lawase). This service activity included pre-tests and post-tests, as well as presentations on how to prepare balance sheets and income statements, and an introduction to accounting applications. All participants showed an increase in knowledge, with post-test scores averaging at least 80. These results indicate that participants have grasped how to prepare balance sheets and income statements, demonstrating that the training materials were effective in enhancing participants' knowledge.